Using Artificial Intelligence to Support Board of Directors in their Roles - Djalilov, Farkhod (Journal of Neonatal Surgery, 2025)
The changing requirements of corporate governance have intensified the strain on board directors to navigate intricate decision-making processes, manage risks, and maintain compliance amid fluctuating market conditions. Artificial Intelligence (AI) has evolved as a disruptive technology that empowers boardrooms through data-driven insights, predictive analytics, and decision support systems. When combined with cloud computing, AI enhances its functionalities via scalable, secure, and real-time collaboration platforms, allowing executives to make educated strategic decisions from any location globally. This article examines how AI-driven solutions, in conjunction with cloud technologies, might mitigate the issues encountered by board directors, including data saturation, risk evaluation, and strategic governance. Primary focal points encompass the utilization of AI for predictive analytics, compliance oversight, and improved decision-making, alongside the function of cloud computing in facilitating unobstructed access to essential information. Empirical case studies demonstrate effective applications of these technologies in executive operations. The study also analyzes the issues, such as ethical considerations, cybersecurity threats, and the necessity for organizational preparedness, that must be resolved for successful implementation. Ultimately, it examines prospective developments in AI and cloud computing, particularly the capacity of generative AI and hybrid cloud systems to further transform board governance. This report emphasizes the imperative of using AI and cloud technologies as essential instruments for contemporary boards to maintain agility, innovation, and competitiveness.